2003
DOI: 10.1097/01.tp.0000061610.34110.04
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of systemic mycoses among renal-transplant recipients in India

Abstract: There is a recent predominance of Aspergillus among the transplant recipients. The risk factors for systemic mycoses are CMV disease, chronic liver disease, and hyperglycemia, and TB is an important coinfection. Systemic mycoses increased in the early postTX period with CsA. The risk factors for death are systemic mycoses, CMV disease, chronic liver disease (>40 months), diabetes mellitus, and Pred+AZA immunosuppression (>2 years). Overall, the probability of survival with systemic mycoses was poor; however, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 19 publications
4
18
0
Order By: Relevance
“…Over the course of 13 years, 0.8% of renal transplant recipients developed cryptococcosis, and most occurred a long time after transplantation. The incidence of cryptococcosis in renal transplant recipients observed in this study was similar to the low incidence rates reported by other groups (0.3%‐5.5%), but with high mortality . Among these 47 patients, the majority had received AMBd (87.2%) as first‐line therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Over the course of 13 years, 0.8% of renal transplant recipients developed cryptococcosis, and most occurred a long time after transplantation. The incidence of cryptococcosis in renal transplant recipients observed in this study was similar to the low incidence rates reported by other groups (0.3%‐5.5%), but with high mortality . Among these 47 patients, the majority had received AMBd (87.2%) as first‐line therapy.…”
Section: Discussionsupporting
confidence: 88%
“…Surgical complications following commercial transplantations have been described as the major cause of morbidity and mortality in both the early and late post-transplant periods. [8][9][10][11][12][13][14]15,17,20,[28][29][30] Consistent with those reports, our current series shows that the rate of surgical complications was quite high. Chugh and Jha reported that it is likely that some of these living-unrelated donor transplantations are performed by questionably qualified physicians in mushrooming private back-street clinics with minimal sanitary facilities.…”
Section: Discussionsupporting
confidence: 81%
“…Chugh and Jha reported that it is likely that some of these living-unrelated donor transplantations are performed by questionably qualified physicians in mushrooming private back-street clinics with minimal sanitary facilities. 20,29,30 It has been reported that commercial living-unrelated transplantations in the Third World have higher rates of serious post-transplantation complications, morbidity and mortality. 1,[8][9][10][11][12][13][14][15][16][17]28,30 Over half of all renal transplant recipients in tropical countries develop serious infection at some point in the post-transplant period and 20% to 40% of them succumb to these infections.…”
Section: Discussionmentioning
confidence: 99%
“…Longer time on HD (due to immunosuppressive effects of ESRD and HD) [2224], pretransplant diabetes mellitus, and chronic liver disease [6, 25] have been pointed as risk factors for developing post-transplant TB. Opportunistic infections (such as caused by CMV, Pneumocystis jiroveci, and Nocardia ) [6, 26] after RT and the presence [22, 25] and number [23] of acute rejection episodes (with IS augmentation) were also associated with increased risk of TB.…”
Section: Discussionmentioning
confidence: 99%